A study on the use of color as an eye relaxant prior to shade selection - Garcia, Estelita L.; Manlapaz, Ma. Theresa P.; Gonzales, Angela (Adviser).
This paper aims to find out the effects of different colors in the accuracy of shade selection and to see which of the colors is the best eye relaxant that would enable the clinicians to accurately match the shade. The subjects for the study were UPCD clinicians diagnosed as color-normal. Using the Trubyte Bioform extended range shade guide, they were asked to match a given unknown shade after looking at a particular color. The control was also tested wherein the clinicians matched the shade without previously looking at any color. There was a statistically significant difference in the accuracy of shade selection among the control and the 4 colors used (red, yellow, green, light blue) and light blue was found to give the most number of accurate selections.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Eye -- Protective devices; Eye -- Psychological aspects; Eye -- Industrial safety